Edukasi Pencegahan Musculoskeletal Disorders pada Buruh Angkut Barang - I Putu Bayu Agus Saputra; Dewi Utary; Siti Ruqayyah; Dwik Putra Nickontara; Muhamad Wahyu Rizal (Insan Kreasi Media, 2023)
Freight workers (porters) operate with a low level of safety. Occupational diseases are illnesses that occur primarily as a result of exposure to risk factors arising from work activities. Musculoskeletal Disorders (MSDs) are conditions that affect the body's musculoskeletal system, including muscles, tendons, ligaments, nerves, discs, and other supporting structures. MSDs are caused by various factors, including repetitive movements, unnatural postures, excessive workload, or a combination of these factors. Porters often suffer from musculoskeletal disorders (MSDs). There is a need for educational materials to be studied by porters to prevent the occurrence of musculoskeletal disorders (MSDs). By using the correct techniques, the risk of injuries such as muscle strain, disc herniation, and joint injuries can be minimized. This was carried out at the Mandalika Bertais market. The method used in this service is the educational method through posters and demonstrations of the correct way to lift loads. The community service began with the preparation and creation of posters as educational media. Education was conducted directly to the porters at the Mandalika Bertais market, attended by 25 people. The educational poster